2016
DOI: 10.1103/physreva.94.053408
|View full text |Cite
|
Sign up to set email alerts
|

Helicity reversion in high-order-harmonic generation driven by bichromatic counter-rotating circularly polarized laser fields

Abstract: We investigate the polarization properties of high harmonics generated with the bichromatic counterrotating circularly polarized (BCCP) laser fields by numerically solving time-dependent Schrödinger equation (TDSE). It is found that, the helicity of the elliptically polarized harmonic emission is reversed at particular harmonic orders. Based on the time-frequency analysis and the classical three-step model, the correspondence between the positions of helicity reversions and the classical trajectories of contin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
(87 reference statements)
3
15
0
Order By: Relevance
“…In the mid-plateau, the right-handed emission from the p + orbital dominates, giving an overall right-handed spectrum, but its contribution drops slightly faster than the p − emission, which dominates closer to the harmonic cutoff. This effect can also be seen on numerical simulations [18,19] and its appearance here in calculations with only the short quantum orbit (with the second return producing harmonics over one order of magnitude weaker, as seen in Fig. 2(c)) provides an alternative to the existing explanations based on the second return's slightly higher harmonic cutoff at excursion times around 300 • /ω [18].…”
Section: Harmonic Spectra and Polarizationsupporting
confidence: 67%
See 2 more Smart Citations
“…In the mid-plateau, the right-handed emission from the p + orbital dominates, giving an overall right-handed spectrum, but its contribution drops slightly faster than the p − emission, which dominates closer to the harmonic cutoff. This effect can also be seen on numerical simulations [18,19] and its appearance here in calculations with only the short quantum orbit (with the second return producing harmonics over one order of magnitude weaker, as seen in Fig. 2(c)) provides an alternative to the existing explanations based on the second return's slightly higher harmonic cutoff at excursion times around 300 • /ω [18].…”
Section: Harmonic Spectra and Polarizationsupporting
confidence: 67%
“…This effect can also be seen on numerical simulations [18,19] and its appearance here in calculations with only the short quantum orbit (with the second return producing harmonics over one order of magnitude weaker, as seen in Fig. 2(c)) provides an alternative to the existing explanations based on the second return's slightly higher harmonic cutoff at excursion times around 300 • /ω [18].…”
Section: Harmonic Spectra and Polarizationsupporting
confidence: 67%
See 1 more Smart Citation
“…The dynamical form of the nonlinear Hall effect manifests in the second harmonic transverse current in response to the linearly polarized light in noncentrosymmetric 2D materials such as biased single and few layer WTe 2 [56][57][58][59][60][61]. Interestingly, theoretical studies provide the direct correspondence of high harmonic helicity (circular dichroism) and topological nature of the electronic band structure [62,63]. For instance, it has been shown that the nonlinear helicity spectroscopy can sharply distinguish between trivial and topological phases of the Haldane model in the hexagonal 2D materials [64,65].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that circularly polarized coherent short wavelength harmonics can be generated by intense counter-rotating bichromatic circularly polarized femtosecond pulses due to the enhancement of electron recollision with parent ions. This capability was demonstrated experimentally only recently , with a potential application to ultrafast X-ray magnetic circular dichroism . There have been many efforts in experiment and theory that are devoted to achieving circularly polarized HHG and attosecond pulses in atoms. Recently, harmonics from degenerate current-carrying orbitals by bichromatic counterrotating circularly polarized pulses have been studied . HHG from 2D solid materials by bicircular fields has been proposed, and it is found that the harmonic polarization depends on the bandgap.…”
Section: Introductionmentioning
confidence: 99%